Examining Time Disruption on Woody Allen’s Midnight in Paris Movie: Magical Realism Study - Irma Puspita Devi (Surakarta English and Literature Journal, 2022)
A good movie directed by Woody Allen, Midnight in Paris (2011), reached marvellous achievement by obtaining 93% on Rotten Tomatoes and massive audiences. This paper focuses on the time disruption shown by Gil Pender's magical journey in Midnight in Paris. It was based on the magical realism elements from the book Ordinary Enchantments Magical Realism and Remystification of Narrative by Wendy B. The aim is to analyze the time disruption caused by Gil Pender's actions and feelings in this movie. This study uses literary textual analysis and attempts to understand the plot and the content to gain the data. The data was collected by identifying the scene and examining the unseen condition of this movie. Time disruption happens between two eras and makes the disruption on time-stamps in this movie. Magical realism sees this as a usual matter. This study shows that the journey of Gil Pender causes and fixes the time stamps itself on Midnight in Paris (2011) movie directed by Woody Allen.